Athenian ostracism and its original purpose a prisoner's dilemma - Węcowski, Marek 1969- (Oxford University Press, 2022)
Ostracism is by far the most emblematic institution of ancient Athenian democracy. This volume offers a reassessment of recently found ostraka (or potsherds, on which the names of the 'candidates' for exile were inscribed by citizens) from several Greek cities outside Athens, a thorough reconstruction of the history and of the procedure of ostracism in Athens, and a comprehensive account of the political circumstances of the introduction of the law on ostracism by Cleisthenes in 508/507 BCE. Marek Wecowski's original study focuses not only on the final stage, the day of the vote, but on the entire operation and procedure of ostracisation
Keywords: History / ukslc; Archaeology / thema; Political alienation / Greece / Athens / History / To 1500; Democracy / Greece / Athens / History / To 1500; Punishment (Greek law); Demokratie; Ostrakismos; Politisches Handeln; Athens (Greece) / Politics and government / To 1500; Athens (Greece) / History / To 1500; Athen